Readiness of Islamic Religious Education Teachers in Implementing The Independent Curriculum at Percut Sei Tuan Junior High School - Pane, Nova Emiliya; Mahariah, Mahariah (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
The curriculum plays a crucial role as a guide for learning. Teachers and the curriculum are like two sides of a coin that must not be separated. The success of curriculum implementation is greatly influenced by the readiness and abilities of teachers, who serve not only as educators but also as curriculum developers. This study aims to analyze the implementation of the independent curriculum planning and the readiness of Islamic Education (PAI) teachers from cognitive, physical, psychological, and financial perspectives in implementing the independent curriculum, ensuring an effective and efficient teaching and learning process. This research employs a qualitative approach with a case study methodology. Data collection techniques include interviews, observations, and documentation. The findings indicate that the planning of the independent curriculum implementation at SMP N 1 Percut Sei Tuan is adequate but not optimal, as it does not fully align with students' interests and talents. PAI teachers are not fully prepared cognitively, as they do not completely understand the independent curriculum and still focus on teacher-centered teaching. Physically, PAI teachers are young, healthy, and capable of effectively utilizing technology in their teaching. Psychologically, PAI teachers demonstrate readiness with high interest and motivation in implementing the independent curriculum. However, financially, readiness is lacking due to inadequate facilities and infrastructure, although PAI teachers continue to be creative in developing learning media.